Controversies in the diagnosis of venous thromboembolism. (June 2015) - Le Gal, G.; Righini, M.
Summary: Over the last decades, important advances have been made in the diagnosis of venous thromboembolism (VTE). Current diagnostic strategies rely on the sequential use of non‐invasive diagnostic tests, based on the pretest clinical probability of disease. Diagnostic tests include D‐dimer measurement, leg vein compression ultrasonography, chest computed tomography pulmonary angiography, or ventilation perfusion (V/Q) lung scan. The safety and cost‐effectiveness of these strategies have been extensively validated. They have been widely implemented in clinical practice and have replaced the historical gold standard diagnostic tests (venography and pulmonary angiography). However, new challenges arise, including a lower clinical suspicion threshold and concerns on potential over‐diagnosis of VTE. Moreover, the diagnostic management remains suboptimal in many subgroups of patients with suspected VTE: patients with prior VTE, pregnant women, or elderly patients.